Lessons From Rocket Science: Reframing the Concept of the Physician Health Advocate. (October 2016) - Hubinette, Maria M.; Regehr, Glenn; Cristancho, Sayra
Abstract : Health advocacy is a prominent component of health professionals' training internationally and is frequently discussed in the medical education literature. Despite this, it continues to be a problematic and challenging topic for medical educators, health professionals, and trainees alike. Borrowing from the field of systems engineering, the authors suggest a need to reconceptualize health advocacy using a systems mind-set rather than a physician-centric perspective. Conceptualizing health advocacy as a systemic, collective effort requires educators, practitioners, and trainees to challenge the assumption that the role of a competent physician health advocate can be fully defined without regard to the larger system or collective within which physicians function. Further, this implies a substantially more dynamic understanding of physicians' and other participants' parts in the collective activity. Of course, this new way of conceptualizing physicians' practices is not limited to health advocacy. The current education paradigm trains physicians for individual competency but expects them to practice collectively. Defining physician competen cies, or the competencies of any health care provider, in isolation from the particular system of which that individual is an integral part implicitly places that health care provider as the central focus of that system. Thus, academic medicine needs to move its educational and research efforts forward in a manner that recognizes that a systems engineering approach to health improvement will allow the various players to maximize their individual efforts to more effectively support the collective activity.